THE PSYCHOLOGICAL IMPACT OF UNJUSTIFIED CHILD REMOVAL BY FINNISH SOCIAL WORKERS - Li, Xingan (Universitas Airlangga, 2026)
ABSTRACT Introduction: This paper examines the psychological consequences of the unjustified removal of a child from our family by social workers in a context where child protection practices have been compromised. Method: The case study presented highlights the child's increased familiarity with terms commonly used by social workers, which subsequently shapes their everyday conversations around foster care, abuse, violence, social workers, child protection, medication, and freedom. Result: The child interprets their previous home experiences, including basic activities such as eating, drinking, and personal hygiene, as instances of violence and abuse. The paper argues that social workers, in their pursuit to justify the removal, meticulously scrutinize every aspect of family life, often fabricating evidence to support their decision. Conclusion: It suggests that such actions are not solely motivated by the welfare of children or the support of families, but rather influenced by the existence of foster care systems established as business chains, leading to an increased demand for children to fill vacancies. The analysis reveals a disconnection between the social workers' actions and factual justifications, as they resort to the creation of narratives based on minute details of family life. Keywords: Child removal, Child protection, Social workers, Foster care, Psychological impact